Hubungan Rawat Gabung Dengan Motivasi Ibu Dalam Memberikan Asi Eksklusif Di RSIA ROSIVA Medan - Pasaribu, Masrina Dewi; Wahyu, Afnijar (Indonesian Trust Nursing Journal, 2025)
Exclusive breastfeeding for 6 months is not as easy as imagined. The coverage of exclusivebreastfeeding is still low because mothers feel that their breast milk is not enough or does notcome out in the first days of the baby's birth, working mothers, and feelings of anxiety aboutfeeling that their breast milk is not enough. Most mothers need support and encouragement inthe form of reliable information so that they can provide their breast milk properly. The objectiveof this study is to determine the relationship between joint care and mothers' motivation toprovide exclusive breastfeeding. This study is a descriptive correlational study with a cross-sectional design. This study will be conducted at RSIA Rosiva Medan. The population is 58people and all of them are used as samples. Sampling is by accidental sampling. The dataused are primary data and secondary data. Data analysis was carried out univariately in afrequency distribution table, and bivariate analysis using the Pearson test with a significancelevel of = 0.05. The study showed that all respondents were 25-35 years old (100%), had ahigh school education (77.1%), and were self-employed (58.3%). The majority of mothers weretreated in joint care (56.3%), and the majority of mothers had moderate motivation to provideexclusive breastfeeding (50.0%). The Pearson test results obtained p-value = 0.000 (p <0.05)meaning that there is a relationship between joint care and maternal motivation to provideexclusive breastfeeding at RSIA Rosiva Medan. It is concluded that the motivation of mothersto provide exclusive breastfeeding is because mothers are joint care with their babies. It isrecommended that further researchers conduct research on maternal motivation to provideexclusive breastfeeding using other variables such as perception, family support, and healthworker support.